The Spectral Theorem for Self-Adjoint Operators - Chilcoat, Kenneth (East Carolina University, 2016)
The Spectral Theorem for Self-Adjoint Operators allows one to define what it means to evaluate a function on the operator for a large class of functions defined on the spectrum of the operator. This is done by developing a functional calculus that extends the intuitive notion of evaluating a polynomial on an operator. The Spectral Theorem is fundamentally important to operator theory and has applications in many fields, especially harmonic analysis on locally compact abelian groups. This thesis represents a merging of two traditional treatments of the Spectral Theorem and includes an extended example highlighting an important application in harmonic analysis.
Keywords: Hilbert Space; Spectral theory (Mathematics); Operator theory; Harmonic analysis